2015
DOI: 10.1371/journal.pone.0134205
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Monitoring in Small Laboratory Mammals Used in Anesthesiology, Respiratory and Critical Care Research: A Systematic Review on the Current Reporting in Top-10 Impact Factor Ranked Journals

Abstract: RationaleThis study aimed to investigate the quality of reporting of anesthesia and euthanasia in experimental studies in small laboratory mammals published in the top ten impact factor journals.MethodsA descriptive systematic review was conducted and data was abstracted from the ten highest ranked journals with respect to impact factor in the categories ‘Anesthesiology’, ‘Critical Care Medicine’ and ‘Respiratory System’ as defined by the 2012 Journal Citation Reports. Inclusion criteria according to PICOS cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 48 publications
3
22
0
4
Order By: Relevance
“…The percent of animals expected to die because of urethane anesthesia, based on empirical observations from our own laboratory, was about 38% (54 of 141 animals). This number appears high, though research has shown that many studies severely under‐report unexpected death from anesthesia (Uhlig et al ). Urethane is a terminal anesthetic and the dose is difficult to adjust.…”
Section: Methodsmentioning
confidence: 99%
“…The percent of animals expected to die because of urethane anesthesia, based on empirical observations from our own laboratory, was about 38% (54 of 141 animals). This number appears high, though research has shown that many studies severely under‐report unexpected death from anesthesia (Uhlig et al ). Urethane is a terminal anesthetic and the dose is difficult to adjust.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, a lower chloral hydrate dose (250 mg/kg) was used to anaesthetize the rats in accordance with some previous studies ( 53 , 54 ). Some studies ( 55 , 56 ) use 300-400 mg/kg chloral hydrate to perform surgery or establish animal models, the process of which requires deep anesthesia and long duration.…”
Section: Discussionmentioning
confidence: 98%
“…The Use of Experimental Refinements in Practice Several structured and systematic literature reviews have given some insight on certain experimental refinements, notably, killing methods (Pound and Nicol, 2018;Uhlig et al, 2015) and the use of anesthetics and analgesics (Bertrand, Sandersen and Flecknell, 2018;Carbone and Austin, 2016;Coulter, Flecknell and Richardson 2009;Coulter et al, 2011;Pound and Nicol, 2018;Richardson, and Flecknell, 2005;Stokes, Flecknell and Richardson, 2009;Uhlig et al, 2015). For example, animal research involving surgical procedures carried out on diverse species and published in peer-reviewed journals has been analyzed with regard to analgesic and anesthetic administration (Coulter et al, 2011;Coulter, Flecknell and Richardson, 2009;Richardson and Flecknell, 2005).…”
Section: 1mentioning
confidence: 99%
“…A systematic review of anesthesia, analgesia and euthanasia methods used in anesthesiology, respiratory and critical care research in top-10 impact factor ranked journals journals pointed to insufficient reporting of experimental studies with small laboratory mammals. Despite the poor reporting, the review found shortcomings in the application of refinement (Uhlig et al, 2015). Another recent attempt to assess trends in pain management, this time in papers published before 2011 and from 2014 to 2015, further confirmed that reporting (and probably the use) of experimental refinement methods is still poor (Carbone and Austin, 2016).…”
Section: 1mentioning
confidence: 99%